가상현실 프로그램이 경직성 뇌성마비 아동의 대동작 기능 및 균형에 미치는 영향 - 이효정; 고지은; Lee, Hyojeong; Go, Jieun (Journal of the Korean Society of Integrative Medicine, 2016)
Purpose : The purpose of this study is to evaluate the effects of virtual reality based exercise program on gross motor function and balance of children with spastic cerebral palsy. Method : Subjects of this study, among the children who received the diagnosis spastic cerebral palsy, for children total of 8 people have agreed to research. Experimental group 4 people, control group 4 people, was a total of 8 people. Group-specific arbitration method, was applied to Nintendo Wii Fit game (experimental group) and exercise program (control group). Each training courses 30 minutes for 4 weeks, examined the changes in Gross Motor Function Measure(GMFM) and Pediatrics Balance Scale(PBS) ability to examine a total of 4-week course effectively. The intervention were compared by measuring before and after. Result : There were significant improvements in the subscales of the gross motor function and balance test of those who practiced with the Nintendo Wii Fit game, while the control group showed no significant changes. Conclusion : Therefore, the virtual based on exercise is effective in improvement of to improve the gross motor function and balance in children with spastic cerebral palsy.